Innovative Development of the Oil and Gas Complex Enterprises Based on Value Added Maximizing Model Realization - E. A. Kuklina (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The reality of the present time is the qualitative complication of mining and geological conditions for the development of oil and gas  resources, which creates higher costs and risks for the participants in the process. The key importance of the Russian oil  and gas sector for the economy of the country makes it necessary to find solutions to minimize the financial losses of oil companies, which will allow enterprises to enter the path of innovative development.  An obligatory condition for the innovative development of enterprises of the oil and gas sector in the modern world space is the choice of  an adequate model of their behavior that reflects the set of changing factors of the external and internal environment. The purpose of the  study is to develop a basic model for maximizing the added value of  an oil and gas company on the basis of alignment of interests. The possibility of applying the model of maximization of value added  by enterprises of the oil and gas sector of Russia is due to the  feature of production and redistribution of value in integrated  structures, such as large oil and gas companies. The implementation of the value-added model will allow the Russian oil and gas sector to  form strategic competitive advantages and create conditions for  balanced sustainable development in the unfavorable situation on  the world markets of hydrocarbon raw materials.